THE EFFECTS OF AUDIT FEES, AUDIT QUALITY AND OWNERSHIP STRUCTURES ON TAX AGGRESSIVENESS: EVIDENCE FROM MANUFACTURING COMPANIES IN INDONESIA - Paramita, I Dewa Ayu Diah Pradnya; Fuad, Fuad (Master of Management, Faculty of Economics and Business, Diponegoro University, 2023)
This study investigates the effect of audit fees, auditors’ quality, and ownership structure on tax aggressiveness in Indonesian manufacturing companies. The sample of this study is based on 132 firm-year observations of IDX-listed companies in Indonesia during the 2018–2021 periods. Our study relies on the panel regression models to test the hypotheses. The results show that audit fees, audit quality with auditor industry specialization proxies, and foreign ownership significantly affect corporate tax aggressiveness. We also find significant differences in tax aggressiveness in the period before and during the Covid-19 pandemic. Our study provides a significant contribution to the accounting literature on how corporate tax aggressiveness is determined by audit characteristics and ownership structure.